Teaching Reading by Using Verbal Football Game - Oktarina, Ria; Haryanto, Haryanto; Oktariansyah, Muhammad; Priuno, Kamus (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2018)
Abstract: The objective of this research is to find out whether or not it is effective to teach reading by using verbal football game to the eighth grade students of Setia Negara Junior High School of Palembang. This research used pre-experimental design. The population of this research was taken from the whole eighth grade students with the total number of students was 61 students. The sample was class VIII.1. There were 30 students are being selected by using convenience non random sampling. The data were collected by using written test and analyzed by using matched t-test calculation. The result of the research showed that there was progress in students? reading skill and achievement. The findings showed that there was a significant difference between the pre-test and post-test results.   Keywords: Teaching Reading, and Verbal Football Game